Negative electrode containing nano hydrophilic-hydrophobic artificial interface protection layer, preparation method of negative electrode and aqueous zinc ion battery
By using nano-hydrophobic and artificial interface protective layer in zinc ion batteries, the problems of zinc negative electrode dendrites and hydrogen evolution are solved, the stability and cycle life of the battery are improved, and the preparation cost is reduced, making it suitable for industrial applications.
Patent Information
- Application Number
- CN202311189280.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2024-12-17
AI Technical Summary
The zinc negative electrode in zinc ion batteries is prone to dendrite and hydrogen evolution reactions during charging and discharging, resulting in damage to the battery's cycle performance and safety. The existing protection methods are complex in preparation, costly and are not suitable for industrialization.
A nano-hydrophobic artificial interface protective layer is formed by reacting hydrophilic polymer, hydrophobic polymer and crosslinking agent. It is loaded on the zinc metal negative electrode material to form a protective layer with a thickness of 50-250 nm to inhibit dendrites' growth and electrode corrosion.
Effectively improves the stability and cycle life of zinc ion batteries, has good compatibility with the interface between the protective layer and zinc negative electrode, is not easy to fall off, regulates the wetting and ion conduction ability of the electrolyte, improves the efficiency and safety of the battery, and is simple to prepare. , low cost.
Smart Images

Figure CN119153615A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer, a preparation method thereof, and an aqueous zinc ion battery. Background Art
[0002] As people's demand for renewable energy continues to increase, zinc-ion batteries, as a new energy storage technology, have the advantages of high energy density, low cost, and environmental friendliness, and are widely used in the fields of energy storage and mobile energy. However, in the actual application of zinc-ion batteries, the zinc negative electrode is prone to produce dendrites during the charging and discharging process, resulting in internal short circuits in the battery, which seriously affects the battery's cycle performance and safety. In addition, hydrogen evolution reactions are prone to occur on the surface of the zinc negative electrode and produce by-products, which will also reduce the capacity and life of the battery. Therefore, protecting the zinc negative electrode has become one of the important ways to improve the stability and cycle life of zinc-ion batteries.
[0003] At present, common zinc negative electrode protection methods include coating with a protective film, adding chemical additives, etc. Among them, coating with a protective film is a relatively effective method, which can prevent dendrite growth and by-product generation by forming a protective layer on the surface of the zinc negative electrode. Chinese patent application CN114005949A discloses a zinc battery negative electrode protected by a hydrophobic layer and a preparation method. The invention is characterized in that a layer of titanate and a hydrophobic binder mixture is provided on the surface of the zinc battery negative electrode active material as a zinc negative electrode protective layer. The protective layer has a certain hydrophobicity and a stable structure, and can effectively inhibit hydrogen evolution at the zinc negative electrode, and can also inhibit zinc dendrites. Chinese patent application CN113097496A discloses a zinc negative electrode with a composite nanofiber protective layer and its preparation and application, the method is to first prepare composite nanofibers through coaxial electrospinning; then remove the sacrificial polymer in the composite nanofibers, that is, obtain porous multi-hollow composite nanofibers; then mix the porous multi-hollow composite nanofibers with an adhesive and a solvent C to obtain a suspension slurry; finally, the suspension slurry is evenly coated on the surface of the zinc negative electrode substrate to obtain a zinc negative electrode with a composite nanofiber protective layer; the prepared zinc negative electrode includes a zinc negative electrode substrate and a protective layer coated on the substrate; the protective layer is mainly composed of porous multi-hollow composite nanofibers stacked; the invention applies the zinc negative electrode with a composite nanofiber protective layer to a zinc-air battery, which significantly improves the battery's cycle stability, coulomb efficiency and safety. Although these methods solve the above-mentioned zinc negative electrode problems to a certain extent, they still have problems such as complex preparation process, easy shedding, high cost and high energy consumption, which are not conducive to the further industrialization of aqueous zinc ion batteries.
[0004] Therefore, it is of great practical significance to find a material that is simple to prepare, low-cost, and effective to prepare a functional coating that can simultaneously inhibit zinc negative electrode dendrite growth and electrode corrosion. Summary of the invention
[0005] The purpose of the present invention is to provide a negative electrode containing a nanometer hydrophilic and hydrophobic artificial interface protective layer in view of the shortcomings of the prior art. The nanometer hydrophilic and hydrophobic artificial interface protective layer is generated by reacting a hydrophilic polymer, a hydrophobic polymer and a cross-linking agent, which can effectively inhibit the growth of dendrites and the generation of by-products in an aqueous zinc ion battery, thereby improving the stability and cycle life of the zinc ion battery.
[0006] One object of the present invention is achieved by the following technical solutions:
[0007] A negative electrode containing a nanometer hydrophilic and hydrophobic artificial interface protective layer, the negative electrode containing the nanometer hydrophilic and hydrophobic artificial interface protective layer comprises a zinc metal negative electrode material and a nanometer hydrophilic and hydrophobic artificial interface protective layer, the nanometer hydrophilic and hydrophobic artificial interface protective layer is formed by reacting raw materials including a hydrophilic polymer, a hydrophobic polymer and a cross-linking agent loaded on the zinc metal negative electrode material.
[0008] Preferably, the thickness of the nano hydrophilic-hydrophobic artificial interface protective layer is 50-250 nm.
[0009] The thickness of the nano hydrophilic and hydrophobic artificial interface protective layer in the present invention does not exceed 250nm, otherwise the protective layer is too thick to prevent ion transmission, causing blockage of the positive and negative electrode reaction areas, and reducing the performance of the battery; and the thickness of the nano hydrophilic and hydrophobic artificial interface protective layer is not less than 50nm, otherwise the protective layer is too thin to form an effective negative electrode protective layer, thereby weakening the protective effect.
[0010] Preferably, the hydrophilic polymer includes one or more of polyvinyl alcohol, polyethylene glycol, polyvinyl alcohol ester, chitosan, and polyacrylic acid.
[0011] More preferably, the hydrophilic polymer is chitosan and / or polyethylene glycol.
[0012] Preferably, the hydrophobic polymer includes one or more of polytetrafluoroethylene, polyacrylamide, and polydimethylsiloxane; more preferably, the hydrophobic polymer is polydimethylsiloxane.
[0013] Further preferably, the hydrophilic polymer is chitosan and / or polyethylene glycol, and the hydrophobic polymer is polydimethylsiloxane. The nanometer hydrophilic and hydrophobic artificial interface protective layer prepared by cross-linking chitosan and / or polyethylene glycol and polydimethylsiloxane has better performance than other hydrophilic polymers and hydrophobic polymers.
[0014] Preferably, the crosslinking agent includes one or more of N,N-methylenebisacrylamide, benzoyl peroxide, divinylbenzene, and isocyanate; more preferably, the crosslinking agent is isocyanate; isocyanate can be listed as toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate.
[0015] Preferably, the zinc metal negative electrode material is zinc foil.
[0016] Preferably, the mass ratio of the hydrophilic polymer, the hydrophobic polymer and the crosslinking agent is (8-15): (8-15): 1. More preferably, the mass ratio of the hydrophilic polymer, the hydrophobic polymer and the crosslinking agent is (9-12): (9-12): 1.
[0017] The preparation method of the nano hydrophilic-hydrophobic artificial interface protective layer is specifically as follows: raw materials including a hydrophilic polymer, a hydrophobic polymer and a cross-linking agent are mixed in an organic solvent to obtain a mixture, the mixture is coated on a zinc metal negative electrode material, and after drying, the nano hydrophilic-hydrophobic artificial interface protective layer loaded on the surface of the zinc metal negative electrode material is obtained.
[0018] The organic solvent is an organic solvent that can dissolve the hydrophilic polymer, the hydrophobic polymer and the crosslinking agent, and examples thereof include toluene, isooctane, xylene, carbon tetrachloride, etc. More preferably, the organic solvent is toluene.
[0019] Preferably, the raw material further comprises a catalyst, and the catalyst is hydrofluoric acid. Further preferably, the added amount of the catalyst is 0.5 to 10 wt % of the hydrophobic polymer.
[0020] Another object of the present invention is achieved by the following technical solutions:
[0021] A method for preparing a negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer comprises the following steps:
[0022] (1) dissolving a hydrophilic polymer and a hydrophobic polymer in an organic solvent to form a mixture A;
[0023] (2) dissolving a cross-linking agent in an organic solvent, adding a catalyst, and standing to form a mixture B;
[0024] (3) ultrasonically dispersing mixture A and mixture B to obtain mixture C;
[0025] (4) The mixture C is evenly scraped onto the zinc metal negative electrode material, and after drying, a negative electrode containing a nano-hydrophilic and hydrophobic artificial interface protective layer is obtained.
[0026] Preferably, the zinc metal negative electrode material is cleaned and dried before use. The cleaning method is not particularly limited, and can be exemplified by ultrasonic cleaning with acetone and / or ethanol. The drying can be vacuum drying or forced air drying.
[0027] Preferably, the drying temperature in step (4) is 20 to 80° C., and the drying time is 10 to 50 hours.
[0028] The third object of the present invention is achieved through the following technical solutions:
[0029] An aqueous zinc ion battery comprises the negative electrode containing the nano hydrophilic and hydrophobic artificial interface protective layer, an electrolyte, a diaphragm and a positive electrode.
[0030] Preferably, the electrolyte is a zinc salt aqueous solution. Further preferably, the zinc salt includes one or more of zinc acetate, zinc sulfate, zinc trifluoromethanesulfonate, zinc tetrafluoroborate, zinc perchlorate, and zinc chloride. Further preferably, it is zinc sulfate.
[0031] Preferably, the concentration of the electrolyte is 0.5 to 5 mol / L; more preferably, 1 to 3 mol / L.
[0032] Preferably, the positive electrode is zinc foil.
[0033] The present invention provides a negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer for use in aqueous zinc ion batteries. The negative electrode is formed by in-situ loading of a hydrophilic polymer, a hydrophobic polymer and a cross-linking agent onto the surface of a zinc metal negative electrode material. Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The nano hydrophilic and hydrophobic artificial interface protective layer of the present invention is formed by reacting a raw material including a hydrophilic polymer, a hydrophobic polymer and a cross-linking agent loaded on a zinc metal negative electrode material. The protective layer has excellent interface compatibility with the zinc negative electrode and is not easy to fall off;
[0035] (2) The protective layer can effectively regulate the wettability of the electrolyte, the mechanical strength of the artificial interface layer, and the ion conductivity;
[0036] (3) The protective layer can protect the zinc negative electrode during the battery cycle, thereby effectively inhibiting the growth of zinc dendrites, improving the battery coulombic efficiency and cycle stability, and thus greatly improving the battery cycle life;
[0037] (4) The protective layer is environmentally friendly and harmless, improving the safety of battery use;
[0038] (5) The method for preparing the nano-hydrophilic-hydrophobic artificial interface protective layer of the present invention has the advantages of simple operation, low cost, significant effect, etc., and is suitable for large-scale production and practical application. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a constant current charge and discharge test curve diagram of the aqueous zinc ion battery of Example 1 and Comparative Example 1;
[0040] Figure 2 It is a constant current charge and discharge test curve diagram of the aqueous zinc ion battery of Example 2 and Comparative Example 1;
[0041] Figure 3 This is a scanning electron microscope image of the aqueous zinc ion battery of Example 1;
[0042] Figure 4 This is a scanning electron microscope image of the aqueous zinc ion battery of Comparative Example 1. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below through specific examples and drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not used for specific limitations of the present invention. The drawings used herein are only for better illustrating the disclosed contents of the present invention and do not have a limiting effect on the scope of protection. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials used in the following examples are purchased through commercial channels unless otherwise specified; the instruments and equipment used in the following examples are all based on the manufacturer's recommended parameters unless otherwise specified.
[0044] In the following examples, the sources of raw materials used are as follows:
[0045] Polydimethylsiloxane is hydroxyl-terminated polydimethylsiloxane, Shanghai Aladdin Biochemical Technology Co., Ltd., CAS: 70131-67-8.
[0046] Chitosan: Qingdao Haihui Bioengineering Co., Ltd., molecular weight 145kD;
[0047] Polyethylene glycol: Jiangsu Yiweici Chemical Co., Ltd., molecular weight 8000;
[0048] Hydrofluoric acid solution: Shanghai MacLean Biochemical Technology Co., Ltd., aqueous solution containing 40v / v% hydrogen fluoride;
[0049] Toluene diisocyanate: Wanhua Chemical TDI-80;
[0050] Diphenylmethane diisocyanate: Wanhua Chemical;
[0051] Polytetrafluoroethylene: Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0052] Polyvinyl alcohol: Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0053] Benzoyl peroxide: Shanghai MacLean Biochemical Technology Co., Ltd.;
[0054] N,N-Methylenebisacrylamide: Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0055] Example 1
[0056] The negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer provided in this embodiment includes a zinc foil and a nano hydrophilic and hydrophobic artificial interface protective layer loaded on the surface of the zinc foil. The raw materials for preparing the nano hydrophilic and hydrophobic artificial interface protective layer are polydimethylsiloxane, chitosan, toluene diisocyanate and hydrofluoric acid solution.
[0057] The preparation method of the negative electrode containing the nano hydrophilic and hydrophobic artificial interface protective layer of this embodiment is as follows:
[0058] (1) 200 g of polydimethylsiloxane and 200 g of chitosan were dissolved in 800 ml of toluene and stirred vigorously to form a uniform mixture A; 20 g of toluene diisocyanate was dissolved in 50 ml of toluene, and 10 g of hydrofluoric acid solution was added, and the mixture was allowed to stand for 40 minutes to form a mixture B;
[0059] (2) adding mixture B to mixture A and dispersing by ultrasonic for 1 hour to obtain mixture C;
[0060] (3) A 100 μm zinc foil was ultrasonically cleaned with acetone and ethanol for 10 minutes respectively, and then dried for later use;
[0061] (4) Evenly scrape a suitable amount of mixture C onto the treated zinc foil and dry it naturally at room temperature for 24 hours to obtain a zinc foil containing a nano hydrophilic-hydrophobic artificial interface protective layer, wherein the thickness of the nano hydrophilic-hydrophobic artificial interface protective layer is 150 nm.
[0062] Assembly of aqueous zinc ion battery: The aqueous zinc ion battery comprises the above-mentioned negative electrode containing the nano hydrophilic and hydrophobic artificial interface protective layer, zinc sulfate electrolyte (2.88 g of zinc sulfate heptahydrate is weighed and dissolved in deionized water to prepare a zinc sulfate solution with a concentration of 2 mol / L), a glass fiber separator and a zinc foil positive electrode. A negative electrode with a diameter of 15 mm and containing a nano hydrophilic and hydrophobic artificial interface protective layer is used as the negative electrode; a zinc foil with a diameter of 15 mm and a thickness of 100 μm treated with acetone and ethanol respectively is used as the positive electrode; a glass fiber with a diameter of 19 mm is selected as the separator, and 200 μL of zinc sulfate electrolyte is evenly dripped on the glass fiber; the battery is assembled in the order of button battery negative electrode shell, shrapnel, gasket, negative electrode, separator, positive electrode, and button battery positive electrode shell.
[0063] Battery Test
[0064] After installing the aqueous zinc ion battery according to the above steps, the battery was left to stand for 2 hours and then charged at 0.5 mA / cm -2 The charge and discharge test was carried out with a current density of 1.54 W.
[0065] Characterization Test
[0066] The battery after the above battery test was disassembled, the negative electrode was taken out, and the negative electrode was cleaned with deionized water and ethanol and then photographed with a scanning electron microscope (SEM).
[0067] The constant current charge and discharge performance test results of Example 1 are shown in Table 1 and Figure 1 As shown, the SEM characterization test results are as follows Figure 3 shown.
[0068] Example 2
[0069] The negative electrode containing a nano-hydrophilic and hydrophobic artificial interface protective layer provided in this embodiment includes a zinc foil and a nano-hydrophilic and hydrophobic artificial interface protective layer loaded on the surface of the zinc foil. The raw materials for preparing the nano-hydrophilic and hydrophobic artificial interface protective layer are polydimethylsiloxane, polyethylene glycol, toluene diisocyanate and hydrofluoric acid solution.
[0070] The preparation method of the negative electrode containing the nano hydrophilic and hydrophobic artificial interface protective layer of this embodiment is as follows:
[0071] (1) 220 g of polydimethylsiloxane and 180 g of polyethylene glycol were dissolved in 800 ml of toluene and stirred vigorously to form a uniform mixture A; 20 g of toluene diisocyanate was dissolved in 50 g of toluene, and 11 g of hydrofluoric acid solution was added, and the mixture was allowed to stand for 30 minutes to form a mixture B;
[0072] (2) adding mixture B to mixture A and dispersing by ultrasonic for 1.5 hours to obtain mixture C;
[0073] (3) A zinc foil with a thickness of 100 μm was ultrasonically cleaned with acetone and ethanol for 8 minutes respectively, and then dried for later use;
[0074] (4) Evenly scrape a suitable amount of mixture C onto the treated zinc foil, and dry it in an oven at 50° C. for 12 hours to obtain a zinc foil containing a nano-hydrophilic and hydrophobic artificial interface protective layer, wherein the thickness of the nano-hydrophilic and hydrophobic artificial interface protective layer is 100 nm.
[0075] The assembly of the aqueous zinc ion battery is the same as that of Example 1.
[0076] The charge and discharge test of the aqueous zinc ion battery is the same as in Example 1, and the test results obtained are shown in Table 1 and Figure 2 shown.
[0077] Example 3
[0078] The negative electrode containing a nano-hydrophilic and hydrophobic artificial interface protective layer provided in this embodiment includes a zinc foil and a nano-hydrophilic and hydrophobic artificial interface protective layer loaded on the surface of the zinc foil. The raw materials for preparing the nano-hydrophilic and hydrophobic artificial interface protective layer are polytetrafluoroethylene, polyethylene glycol, benzoyl peroxide and hydrofluoric acid solution.
[0079] The preparation method of the negative electrode containing the nano hydrophilic and hydrophobic artificial interface protective layer of this embodiment is as follows:
[0080] (1) 240 g of polydimethylsiloxane and 200 g of polyethylene glycol were dissolved in 900 ml of toluene and stirred vigorously to form a uniform mixture A; 20 g of benzoyl peroxide was dissolved in 50 g of toluene, and 12 g of hydrofluoric acid solution was added, and the mixture was allowed to stand for 50 minutes to form a mixture B;
[0081] (2) adding mixture B to mixture A and ultrasonically dispersing for 80 min to obtain mixture C;
[0082] (3) A zinc foil with a thickness of 100 μm was ultrasonically cleaned with acetone and ethanol for 12 minutes respectively, and dried for later use;
[0083] (4) Evenly scrape a suitable amount of mixture C onto the treated zinc foil, and dry it in an oven at 40° C. for 18 hours to obtain a zinc foil containing a nano-hydrophilic and hydrophobic artificial interface protective layer, wherein the thickness of the nano-hydrophilic and hydrophobic artificial interface protective layer is 100 nm.
[0084] The assembly of the aqueous zinc ion battery is the same as that of Example 1. The charge and discharge test of the aqueous zinc ion battery is the same as that of Example 1, and the constant current charge and discharge performance test results obtained are shown in Table 1.
[0085] Example 4
[0086] The negative electrode containing a nano-hydrophilic and hydrophobic artificial interface protective layer provided in this embodiment includes a zinc foil and a nano-hydrophilic and hydrophobic artificial interface protective layer loaded on the surface of the zinc foil. The raw materials for preparing the nano-hydrophilic and hydrophobic artificial interface protective layer are polydimethylsiloxane, polyvinyl alcohol, diphenylmethane diisocyanate and hydrofluoric acid solution.
[0087] The preparation method of the negative electrode containing the nano hydrophilic and hydrophobic artificial interface protective layer of this embodiment is as follows:
[0088] (1) 180 g of polydimethylsiloxane and 220 g of polyethylene glycol were dissolved in 900 ml of toluene and stirred vigorously to form a uniform mixture A; 20 g of diphenylmethane diisocyanate was dissolved in 50 g of toluene, and 11 g of hydrofluoric acid solution was added, and the mixture was allowed to stand for 60 minutes to form a mixture B;
[0089] (2) adding mixture B to mixture A and ultrasonically dispersing for 70 min to obtain mixture C;
[0090] (3) A zinc foil with a thickness of 100 μm was ultrasonically cleaned with acetone and ethanol for 12 minutes respectively, and dried for later use;
[0091] (4) Evenly scrape a suitable amount of mixture C onto the treated zinc foil, and dry it in an oven at 50° C. for 13 hours to obtain a zinc foil containing a nano-hydrophilic and hydrophobic artificial interface protective layer, wherein the thickness of the nano-hydrophilic and hydrophobic artificial interface protective layer is 150 nm.
[0092] The assembly of the aqueous zinc ion battery is the same as that of Example 1. The charge and discharge test of the aqueous zinc ion battery is the same as that of Example 1, and the constant current charge and discharge performance test results obtained are shown in Table 1.
[0093] Comparative Example 1
[0094] The difference between Comparative Example 1 and Example 1 is that the negative electrode of Comparative Example 1 does not include a nano-hydrophilic and hydrophobic artificial interface protective layer.
[0095] The assembly of the aqueous zinc ion battery is the same as that of Example 1.
[0096] The aqueous zinc ion battery prepared in Comparative Example 1 was subjected to battery testing and characterization testing. The constant current charge and discharge performance test results are shown in Tables 1 and Figure 1 The characterization test results are shown in Figure 4 shown.
[0097] The SEM characterization test results of Example 1 and Comparative Example 1 are as follows: Figure 3 and Figure 4 As shown. Figure 3 and Figure 4 By comparison, it can be seen that after cycling the zinc negative electrode without a nano-hydrophilic-hydrophobic artificial interface protective layer, the negative electrode has obvious dendrite growth, and the dendrites are stacked in large blocks; while after cycling the zinc negative electrode with a nano-hydrophilic-hydrophobic artificial interface protective layer, the surface of the zinc negative electrode presents a dendrite-free, dense and uniform morphology.
[0098] Comparative Example 2
[0099] The difference between Comparative Example 2 and Example 1 is that the raw material of the protective layer of Comparative Example 1 does not include chitosan. The specific preparation method of the negative electrode containing the protective layer is as follows:
[0100] (1) 200 g of polydimethylsiloxane was dissolved in 800 ml of toluene and stirred vigorously to form a uniform mixture A; 20 g of toluene diisocyanate was dissolved in 50 g of toluene, and 10 g of hydrofluoric acid solution was added, and the mixture was allowed to stand for 40 minutes to form a mixture B;
[0101] Steps (2), (3) and (4) are the same as those in Example 1.
[0102] The assembly of the aqueous zinc ion battery is the same as that of Example 1. The charge and discharge test of the aqueous zinc ion battery is the same as that of Example 1, and the constant current charge and discharge performance test results obtained are shown in Table 1.
[0103] Comparative Example 3
[0104] The difference between Comparative Example 3 and Example 1 is that the raw material of the protective layer of Comparative Example 3 does not include polydimethylsiloxane. The specific method for preparing the negative electrode containing the protective layer is as follows:
[0105] (1) 200 g of chitosan was dissolved in 800 ml of toluene and stirred vigorously to form a uniform mixture A; 20 g of toluene diisocyanate was dissolved in 50 g of toluene, and 10 g of hydrofluoric acid solution was added, and the mixture was allowed to stand for 40 minutes to form a mixture B;
[0106] Steps (2), (3) and (4) are the same as those in Example 1.
[0107] The assembly of the aqueous zinc ion battery is the same as that of Example 1. The charge and discharge test of the aqueous zinc ion battery is the same as that of Example 1, and the constant current charge and discharge performance test results obtained are shown in Table 1.
[0108] Comparative Example 4
[0109] The difference between Comparative Example 4 and Example 1 is that the raw material of the protective layer of Comparative Example 4 does not include a cross-linking agent. The specific method for preparing the negative electrode containing the protective layer is as follows:
[0110] (1) 200 g of polydimethylsiloxane and 200 g of chitosan were dissolved in 800 ml of toluene and stirred vigorously to form a uniform mixture A; 10 g of hydrofluoric acid solution was added to 50 g of toluene and allowed to stand for 40 minutes to form a mixture B;
[0111] Steps (2), (3) and (4) are the same as those in Example 1.
[0112] The assembly of the aqueous zinc ion battery is the same as that of Example 1. The charge and discharge test of the aqueous zinc ion battery is the same as that of Example 1, and the constant current charge and discharge performance test results obtained are shown in Table 1.
[0113] Comparative Example 5
[0114] The difference between Comparative Example 5 and Example 1 is that the thickness of the nano hydrophilic-hydrophobic artificial interface protective layer in Comparative Example 5 is 350 nm.
[0115] The assembly of the aqueous zinc ion battery is the same as that of Example 1. The charge and discharge test of the aqueous zinc ion battery is the same as that of Example 1, and the constant current charge and discharge performance test results obtained are shown in Table 1.
[0116] Comparative Example 6
[0117] The difference between Comparative Example 6 and Example 1 is that the thickness of the nano hydrophilic-hydrophobic artificial interface protective layer in Comparative Example 6 is 20 nm.
[0118] The assembly of the aqueous zinc ion battery is the same as that of Example 1. The charge and discharge test of the aqueous zinc ion battery is the same as that of Example 1, and the constant current charge and discharge performance test results obtained are shown in Table 1.
[0119] Table 1 Constant current charge and discharge test results of each embodiment and comparative example
[0120] Number of cycles Cycle life / h Example 1 325 650 Example 2 300 600 Example 3 200 400 Example 4 240 480 Comparative Example 1 30 60 Comparative Example 2 50 100 Comparative Example 3 60 120 Comparative Example 4 100 200 Comparative Example 5 130 260 Comparative Example 6 90 180
[0121] It can be seen from the above embodiments and comparative examples that the nano-hydrophilic and hydrophobic artificial interface protective layer prepared by the present invention can protect the zinc negative electrode during the battery cycle, thereby effectively inhibiting the growth of zinc dendrites, improving the battery coulombic efficiency and cycle stability, and thus greatly improving the battery cycle life.
[0122] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0123] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.
[0124] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer, characterized in that: The negative electrode containing the nano hydrophilic and hydrophobic artificial interface protective layer comprises a zinc metal negative electrode material and a nano hydrophilic and hydrophobic artificial interface protective layer, wherein the nano hydrophilic and hydrophobic artificial interface protective layer is formed by reacting raw materials including a hydrophilic polymer, a hydrophobic polymer and a crosslinking agent loaded on the zinc metal negative electrode material.
2. The negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer according to claim 1, characterized in that: The thickness of the nano hydrophilic-hydrophobic artificial interface protective layer is 50-250 nm.
3. The negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer according to claim 1, characterized in that: The hydrophilic polymer includes one or more of polyvinyl alcohol, polyethylene glycol, polyvinyl alcohol ester, chitosan, and polyacrylic acid.
4. The negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer according to claim 1, characterized in that: The hydrophobic polymer includes one or more of polytetrafluoroethylene, polyacrylamide, and polydimethylsiloxane; and / or, the cross-linking agent comprises one or more of N,N-methylenebisacrylamide, benzoyl peroxide, divinylbenzene, and isocyanate; And / or, the zinc metal negative electrode material is zinc foil.
5. A negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer according to claim 1 or 3, characterized in that: The hydrophilic polymer is chitosan and / or polyethylene glycol.
6. A negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer according to claim 1 or 4, characterized in that: The hydrophobic polymer is polydimethylsiloxane, and the cross-linking agent is isocyanate.
7. The negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer according to claim 1, characterized in that: The mass ratio of the hydrophilic polymer, the hydrophobic polymer and the cross-linking agent is (8-15):(8-15):
1.
8. The negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer according to claim 1, characterized in that: The raw materials also include a catalyst, and the catalyst is hydrofluoric acid.
9. A method for preparing a negative electrode containing a nano hydrophilic and hydrophobic artificial interface protective layer, characterized in that: The following steps are involved: (1) dissolving a hydrophilic polymer and a hydrophobic polymer in an organic solvent to form a mixture A; (2) dissolving a cross-linking agent in an organic solvent, adding a catalyst, and standing to form a mixture B; (3) ultrasonically dispersing mixture A and mixture B to obtain mixture C; (4) The mixture C is evenly scraped onto the zinc metal negative electrode material, and after drying, a negative electrode containing a nano-hydrophilic and hydrophobic artificial interface protective layer is obtained.
10. An aqueous zinc ion battery, characterized in that: The aqueous zinc ion battery comprises the negative electrode containing the nano hydrophilic and hydrophobic artificial interface protective layer according to claim 1 or the negative electrode containing the nano hydrophilic and hydrophobic artificial interface protective layer prepared by the preparation method of claim 9, an electrolyte, a separator and a positive electrode.
